Mirmecofauna de solo e vegetação em áreas com muita e pouca cobertura arbórea no Cerrado da RPPN de galheiro (CEMIG), Perdizes-MG - Marques, Graziella Diogenes Vieira (2005)
The present study investigated the diversity of ant fauna in the ground and vegetation of an ecological reserve in cerrado. The aim of this study was to characterize the differences in some environmental variables, mainly related to the vegetation structure and seasonality. The ant fauna sampling was made monthly between April 2002 and December 2003 in areas with little forest coverage (APCA; 0% - 35%) and in others with high forest coverage (AMCA; > 35%). The samples were made with sardine baits in four distinct combined conditions (soil or vegetation, diurnal or nocturnal), during two periods o f the year (dry and wet season). A total of 72 ant species were collected, belonging to 18 genera and six subfamilies. Camponotus (25) species was the most common genera, followed by Pheidole (10) species. The major diversity values (Shannon index) were found for areas with little forest coverage and in relation to the type o f substrate, the most diversity was found in vegetation. Assembly analyses revealed the composition o f two groups, the genera that were most frequent in the soil (Atta, Eciton, Ectatomma, Neivamyrmex, Linepithema, Odontomachus, Pheidole e Solenopsis) and that most frequent in vegetation (Brachymyrmex, Camponotus, Cephalotes, Crematogaster, Gnamptogenys, Heteroponera, Paratrechina e Pachycondyla). There was no seasonal difference in the occurrence o f genera between dry and wet season. The present study point out to the necessity of combined methodologies for an efficient ant fauna sampling. It also verified that the studies o f seasonality can be useful to identify the temporal composition of species o f an area and that the assembly analyses are essential tools to evidence the possible local guilds.